PENGARUH TERAPI BEKAM BASAH TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - Rosida, Ida; Nurahmi, Irma (Coping: Community of Publishing in Nursing; Vol 4 No 3 (2016): Desember 2016, 2016)
Hypertension often called the silent killer, because hypertension is a disorder of without symptoms, but if overlooked and allowed within a long time can result in permanent damage on vital organs of the body like the brain, the kidneys, and heart. Therefore, necessary treatment to overcome hypertension. The treatment of hypertension is divided into two categories namely pharmacological and non pharmacological. Cupping is one type of complementary therapy non pharmacological that can be used for patients hypertension. The purpose of this research is to find the existence of the influence of wet cupping therapy against of blood pressure in patients hypertension in Rumah Sehat Cordova Tasikmalaya City. Methods used namely pre experimental to a draft one group pretest-posttest design. Total population is 36 people. And samples taken is 20 people by purposive applying a technique of sampling. An instrument used is sphygnomanometer mercury, a stethoscope, and sheets of stuffing. This research using analysis bivariat Wilcoxon test. Wet cupping therapy got having significant influence on blood pressure in patients of hypertension with the value of p value 0,001 ? 0.05 (for BP systolic) and 0,000 ? 0.05 (for BP diastolic). In conclusion, wet cupping may affect blood pressure in patients hypertension. Because of it, hopefully the medical team especially nurse can use complementary therapy wet cupping in dealing with patients hypertension. Keyword                : Blood Pressure, Hypertension, Wet Cupping